2010
DOI: 10.1002/biof.93
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LPS‐inducible genes downregulated by ubiquinone in human THP‐1 monocytes

Abstract: Coenzyme Q(10) (CoQ(10)) is an obligatory element in the respiratory chain and functions as a potent antioxidant of lipid membranes. More recently, anti-inflammatory effects as well as an impact of CoQ(10) on gene expression have been observed. To reveal putative effects of Q(10) on LPS-induced gene expression, whole genome expression analysis was performed in the monocytic cell line THP-1. Thousand one hundred twenty-nine and 710 probe sets have been identified to be significantly (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Genome-scale transcriptional responses of protein-coding genes following lipopolysaccharide (LPS)-induced activation of the innate immune response in human monocytes and monocytic cell lines have been extensively studied using both microarrays1 and serial analysis of gene expression23. These studies have clearly demonstrated the induction of many members of proinflammatory cytokines (for example, IL1β, CXCL8, IL6 and tumor necrosis factor alpha ( TNFα )), chemokines and cell surface markers in response to Toll-like receptor 4 (TLR4) signalling3.…”
mentioning
confidence: 99%
“…Genome-scale transcriptional responses of protein-coding genes following lipopolysaccharide (LPS)-induced activation of the innate immune response in human monocytes and monocytic cell lines have been extensively studied using both microarrays1 and serial analysis of gene expression23. These studies have clearly demonstrated the induction of many members of proinflammatory cytokines (for example, IL1β, CXCL8, IL6 and tumor necrosis factor alpha ( TNFα )), chemokines and cell surface markers in response to Toll-like receptor 4 (TLR4) signalling3.…”
mentioning
confidence: 99%
“…CoQ 10 is a known modulator of gene expression [4,5] and inflammatory processes [7-9]. Because the reduced form of CoQ 10 , ubiquinol, is a potent antioxidant that protects lipids, DNA and proteins from oxidative damage [12-14], we examined the effect of Q 10 H 2 supplementation on both serum GGT and AST activity as potential markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma C-reactive protein (CRP) concentrations were measured using a latex enhanced nephelometric assay run on a BN II hematology analyzer (Dade Behring, Marburg, Germany). Microarray experiments using the Affymetrix human genome U133 plus 2.0 GeneChip® were performed as previously described [5] with RNA samples from CD14-positive monocytes obtained from three volunteers before (T 0 ) and after (T 14 ) supplementation with ubiquinol.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, CoQ 10 could act as an antioxidant, preventing oxidative damage of lipids, proteins and DNA [7,8]. Moreover, CoQ 10 has been identified as a modulator of gene expression [9, 10] and is necessary for the function of uncoupling proteins [11] and pyrimidine biosynthesis [12]. The percentage of the oxidized form of CoQ increases with age, indicating a decreased anti-oxidative capacity of aged individuals [13].…”
Section: Introductionmentioning
confidence: 99%